Liver histopathological alteration and dysfunction after bisphenol A administration in male rats and protective effects of naringin - Masoud Mahdavinia; Layasadat Khorsandi; Soheila Alboghobeish; Azin Samimi; Mohammad Amin Dehghani; Leila Zeidooni (Mashhad University of Medical Sciences, 2021)
Objective: Bisphenol A (BPA) is an organic synthetic compound, often used in manufacturing polycarbonate plastics. Researches have shown the role of BPA as an endocrine disruptor. The present study intended to evaluate the hepatoprotective properties of naringin, an active flavanone glycoside present in many citrus fruit, against hepatotoxicity induced by BPA. Materials and Methods: Male Wistar rats were orally treated with 50 mg/kg BPA for 30 consecutive days for induction of toxicity and 40, 80 and 160 mg/kg naringin for the same period along with BPA or alone. Results: This study demonstrated that BPA significantly increased serum levels of triglyceride, lactate dehydrogenase (LDH), alkaline phosphatase (ALP), lipid peroxidation, and aspartate aminotransferase (AST) and significantly reduced catalase, glutathione peroxidase (GPx) and superoxide dismutase (SOD) activity, glutathione (GSH) and caused periportal inflammation and microvesicular steatosis in rat tissue. However, BPA did not change serum levels of high-density lipoprotein-cholesterol (HDL-C), total cholesterol, alanine aminotransferase (ALT), or low-density lipoprotein-cholesterol (LDL-C). Furthermore, the results displayed that administration of 80 and 160 mg/kg naringin improved hepatotoxicity and altered lipid peroxidation level, serum values of triglyceride and liver enzymes, and oxidative stress factors that were induced by BPA. The effect of two doses of 80 and 160 mg/kg naringin was more noticeable than that of dose 40 mg/kg. Conclusion: The findings suggested the protective effects of naringin against BPA-induced hepatotoxicity via ameliorating liver histopathological alteration, suppressing oxidative stress and lipid-lowering properties.